(untitled) (Annual of the Faculty of Philosophy in Skopje, 2007)
The sociological aspect in the analysis of globalization consists in the tendency to integrate various aspects (economic, political, technical, ecological) in the study of the contemporary world as a world of connected individuals, connected enterprises, connected institutions and organizations. In this conception, an optimistic dimension of globalization and a pessimistic dimension of globalization come to the fore, which are still connected in a mechanical way. This paper presents several considerations on the basis of optimistic visions of globalization, and on which the pessimistic views of globalization are based. The Macedonian case of globalization is also presented, where a high percentage of social risk is noted, which is one of the consequences of globalization. The analysis is supported by data from the SEESSP survey conducted in the Republic of Macedonia in 2003.